RANCANG BANGUN SISTEM INFORMASI ASET PADA MTS SIROJUL ATHFAL MENGGUNAKAN FRAMEWORK CODEIGNITER 3.0 - Kasruddin, Muhammad Ikhsan; Suhendra Anjar Dinata; Bagus Wahyu Pandhito (Sekolah Tinggi Ilmu Komputer El Rahma, 2025)
An efficient and well-organized information system is a crucial component in school asset management to enhance the effectiveness of asset management and maintenance. This study aims to design and implement an asset information system at Madrasah Tsanawiyah (MTs) Sirojul Athfal using the CodeIgniter 3.0 framework. Data were collected through interviews, observations, and literature reviews to understand user needs and business processes related to school asset management. The resulting information system includes features such as inventory management, asset tracking, maintenance reporting, and user management. Testing demonstrated that this system effectively assists MTs Sirojul Athfal in managing assets more efficiently and systematically.